Research hot topics and evolutionary analysis of Taichi in China based on knowledge map - Zhao, Jiajia; Xu, Aie; Zhou, Wenhao; Zhao, Zikun (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: This study takes the relevant papers on Taichi in the past 10 years from 2012 to 2022 included in the China Knowledge Network Database (CNKI) as the research object, and uses CiteSpace visualization and analysis software to scientifically measure and visually analyze the nearly 874 domestic relevant research documents, and by constructing the knowledge map of Taichi movement, we can By constructing a knowledge map of Taichi movement, it can clearly present the evolution of Taichi movement and research hotspots. Through the analysis of the number of articles published, keyword co-occurrence mapping, cluster mapping and research process analysis, it is found that the current research hotspots of Taichi include the relationship between Taichi and health, Taichi and the elderly, and Taichi and mental health, and so on. With the improvement of health awareness and the increase of the elderly population, more and more studies focus on the role of Taichi in promoting physical and mental health. In addition, the research on Taichi exercise in the last decade presents a dynamic evolution process, and according to its evolution trend, it can be understood that the research trend of Taichi exercise in China will tend to the fitness effect of Taichi, its comparison with other fitness modalities, and the evaluation of the effect. In this paper, CiteSpace analysis tools are used in order to explain the hotspots and evolutionary process of the research on Taichi exercise in China, and to provide a reference for further research in this field.